2003
DOI: 10.1093/jn/133.11.3987s
|View full text |Cite
|
Sign up to set email alerts
|

Formative Research to Develop a Nutrition Education Intervention to Improve Dietary Iron Intake among Women and Adolescent Girls through Community Kitchens in Lima, Peru

Abstract: Formative research was conducted with 26 women and 16 adolescent girls to develop an education intervention through community kitchens (CK) in Lima, to increase their dietary iron intake and improve their iron status. A combination of qualitative research methods was used to explore perceptions about foods, nutrition, health, anemia and body image. The women recognized that there was a close association among eating well, "alimentarse bien", their health and prevention and treatment of anemia. They perceived t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 5 publications
2
27
0
Order By: Relevance
“…Increased DD was dependent on WDL membership which aligns with other research that reported greater success of nutrition interventions when accompanied by agricultural development [38]. This is consistent with previous research that found WDL members had higher income and greater food security [15] and with the anecdote that members obtained staple foods on credit from WDL and purchased vegetables and fruit using their casual income [13].…”
Section: Iron and Zinc Intakesupporting
confidence: 88%
See 1 more Smart Citation
“…Increased DD was dependent on WDL membership which aligns with other research that reported greater success of nutrition interventions when accompanied by agricultural development [38]. This is consistent with previous research that found WDL members had higher income and greater food security [15] and with the anecdote that members obtained staple foods on credit from WDL and purchased vegetables and fruit using their casual income [13].…”
Section: Iron and Zinc Intakesupporting
confidence: 88%
“…In the context of this research, the intervention also addressed a belief that eating fruits and vegetables was less important than eating starchy cooked "food" [13] and increased the proportion of women who factored "health/being good for me" into their food choices [16]. The sustainability of this intervention is uncertain, given the limitations of a single intervention session and the recognition that longer duration participatory approaches have been more successful [29,38,39]. The pre-existing relationship may have reduced the need for extensive work to gain community participation, which appeared to be the case, given the high level of participation.…”
Section: Iron and Zinc Intakementioning
confidence: 99%
“…First, it provides an opportunity to conduct formative work on the content and delivery method of health communication interventions prior to a large scale trial. Formative work has been shown to be a key component of behavioral interventions and allows for greater success in achieving behavior change among participants (Coreil et al, 1998; Corneli et al, 2007; Creed-Kanashiro et al, 2003). Second, it allows for the design of theory-based media and then the ability to test the theory in a laboratory setting, enabling the examination of both psychosocial and physiological variables.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these and other factors in the conceptual model have been identified by others as constraints on feeding animal-source foods or raising livestock, or as factors addressed in interventions: livestock feed supply [14], poor animal health [14,15], climate [14], cost of animal-source foods [13], farmers' resources to maintain and improve livestock productivity [15], farmers' limited access to credit [15], selling but not eating livestock [58], inadequate feed technology and processing [59], negative perception of animal-source foods [60][61], and cultural norms and religious taboos about consumption of animal-source foods [13].…”
Section: Community Household and Individual Constraintsmentioning
confidence: 99%